Developing A Module of Guidance’s School Accreditation For School’s Stakeholders - Sari, Wiwin Angita; Kristiawan, Muhammad; Arafat, Yasir (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2022)
Some primary schools in Palembang got problems related to the implementation of the school’s accreditation. This research aimed at producing a module of guidance’s school accreditation for school’s stakeholders which valid, practical and effective. This research used Research and Development (R&D). The model development in this study used 4-D (Define, Design, Develop, and Disseminate). The objects of this research were the State Primary school 21, 22 and 29 in Palembang. The results concluded that the module was declared valid, practical and effective. This paper contribute to all educational stakeholders in primary, secondary and high education as an alternative module which can help to prepare accreditation.